2008
DOI: 10.1017/s0142716408080016
|View full text |Cite
|
Sign up to set email alerts
|

Bilingual children with language impairment: A comparison with monolinguals and second language learners

Abstract: The purpose of this study is twofold: (a) to examine whether English finite morphology has the potential to differentiate children with and without language impairment (LI) from Spanish-speaking backgrounds and different levels of English proficiency in comparison to Hispanic English speakers and (b) to investigate the extent to which children who are bilingual exhibit differences in their grammatical performance because of cross-linguistic influence from their first language. Seventy-one children between the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
102
5
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(124 citation statements)
references
References 28 publications
13
102
5
4
Order By: Relevance
“…Children with English exposure rates at or below 30% input and output at school and at home were misclassified (false positives and false negatives) 29% of the time, compared to 17% misclassification of children who had exposure rates above 30%. These findings are consistent those of Gutiérrez-Clellen et al (2008). In that study, the ELL children with less than 30% exposure to English at home were the most likely to be misclassified.…”
Section: The Influence Of Language Exposuresupporting
confidence: 89%
“…Children with English exposure rates at or below 30% input and output at school and at home were misclassified (false positives and false negatives) 29% of the time, compared to 17% misclassification of children who had exposure rates above 30%. These findings are consistent those of Gutiérrez-Clellen et al (2008). In that study, the ELL children with less than 30% exposure to English at home were the most likely to be misclassified.…”
Section: The Influence Of Language Exposuresupporting
confidence: 89%
“…Another common methodological approach is to assess current bilingual exposure and to select only children who receive a certain percentage of bilingual input each week (as in Gutierrez-Clellen et al 2008). However, a major limitation of this approach is that it does not account for changes in language use over time.…”
Section: Participantsmentioning
confidence: 99%
“…Research on bilingual exposure in children with specific language impairment (Gutierrez-Clellen et al 2008;Paradis et al 2003) and Down Syndrome (Feltmate and Kay-Raining Bird 2008;Kay-Raining Bird et al 2005) found no additional language delays in bilingually-exposed participants. These studies had small numbers of participants in the language-impaired bilingual exposure groups (e.g., 4-11), and participation was generally limited to children with 'intensive' bilingual exposure and productive expressive bilingual abilities.…”
Section: Introductionmentioning
confidence: 97%
“…As Serratrice and Hervé (2015) note, the studies conducted by Juan-Garau and Pérez-Vidal (2000), , SilvaCorvalán (2014), and Zwanziger et al (2005) did not find evidence in support of CLI based on the relative proportion of null and overt subjects in children's naturalistic productions (see also Gutiérrez-Clellen, Simon-Cerejido, andWagner, 2008 andLiceras et al, 2012); their performance regarding the rate of non-overt and lexical subjects was reminiscent of that of monolinguals, challenging the CLI hypothesis. Nonetheless, Serratrice and Hervé (2015) emphasize the need to investigate the issue of whether subjects are pragmatically appropriate, since CLI is tightly connected to the interface between syntax and semantics/pragmatics, a consideration that was indeed taken into account by some studies.…”
Section: The Crosslinguistic Influence Hypothesis Regarding Subjecthoodmentioning
confidence: 96%